Prediction of Internet Addiction and Social Anxiety Based on Parenting Styles in Adolescents of Sabzevar, Iran - Elahe Sadat Tabatabaeirad; Afzal Akbari Balootbangan (Hamadan University of Medical Sciences, 2017)
Background and Objectives: Parenting styles are one of the most important factors in shaping adolescents' behaviors and personality. Therefore, we aimed to predict internet addiction and social anxiety based on parenting styles. Materials and Methods: This descriptive and correlational study was performed in 400 high school students of Sabzevar, Iran, in 2015. The participants were selected using multi-stage cluster sampling method. The data were collected using Yang's Internet Addiction Test (IAT), Social Anxiety Scale (SAS-A), and Baumrind's Parenting Styles Questionnaire. To analyze the data, Pearson correlation coefficient and multiple regression were run in SPSS, version 22. Results: We found a significant positive correlation between the authoritarian and permissive parenting styles and Internet addiction (r=0.102, r=0.210, respectively) and social anxiety (r=0.576, r=0.517, respectively). Moreover, a significant negative correlation was observed between the authoritative parenting style and Internet addiction and social anxiety (r= -0.291 and r= -0.263, respectively). In addition, multiple regression analysis reflected that the parenting styles could predict Internet addiction and social anxiety, and they explained respectively 39% and 35% of the variance. Conclusions: According to the results, adopting proper educational methods and implementing practical plans can predict Internet addiction and improve positive relationships among individuals.